Do sustainability reports contain financially material information? - Haley, Suzanne; Shaffer, Matthew; Sloan, Richard (Review of Accounting Studies, 2026)
Abstract Recent years have witnessed significant growth in corporate sustainability reporting. Yet existing research provides mixed evidence on the information content of these reports for investors. We examine the stock market reaction to the announcement of a sample of US corporate sustainability reports incorporating Sustainability Accounting Standards Board metrics that are intended to provide financially material information to investors. Using standard measures of information content, we cannot find compelling evidence that these reports provide a significant amount of new information to investors. Further analysis of a subset of common metrics indicates that they are either financially immaterial or preempted by traditional financial disclosures. Finally, we show that most firms target their sustainability reports at a broad set of sustainability-oriented stakeholders rather than a narrow set of financially oriented investors.